A prospective interventional study of intra-caesarean copper intrauterine contraceptive devices insertion in a teaching hospital in a rural medical college in Telangana, India - Vijayalakshmi, Gillella; Kothapally, Kavitha; Bhashyakarla, Uma; Kavati, Vasantha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Providing quality contraceptive services to women is essential for achieving maternal and child health. Objective of this study was to evaluate the efficacy of intra-caesarean insertion of copper IUCDs as postpartum contraception. To study the side effects of intra caesarean copper device. To study the continuation rates of intra-caesarean copper IUCDs. To study the acceptability of intra-caesarean copper IUCD as immediate postpartum contraceptive. Methods: The prospective study was undertaken at Bhaskar medical college and general hospital, Yenkepally, Moinabad, Telangana, between January 2016 and March 2018 after ethical committee clearance. About 60 pregnant women were enrolled into the study after an informed written consent regarding the procedure, benefits and complications and the need for follow up for at least one year. Copper T 380A/multiload copper 375 was inserted into the uterine cavity after delivery of the placenta and membranes during caesarean section. Patients were followed up at 6 weeks, 6 months and one-year intervals for any complaints, visibility of threads and for ultrasound examination for position of copper IUCDs in the uterus. Data analysis was done using Microsoft excel 2016. Results: Nearly 48.33% continued intra-caesarean copper IUCDs for more than 1 year. 70% did not have any complaints. 86.67% came for more than one follow-up visit. 47% had copper IUD threads visible by one year. No case of perforation either during insertion or during continuation was noted. None conceived with copper IUCD in situ. Removal of copper IUCD was also easy and none required hysteroscopic removal. Conclusions: Intra-caesarean copper IUCD insertion is a safe and effective long acting reversible contraceptive method in the postpartum period.